2014
DOI: 10.1093/eurpub/cku151.018
|View full text |Cite
|
Sign up to set email alerts
|

Non-publication and delayed publication of randomized trials on vaccines: a survey

Abstract: Objective To evaluate the extent of non-publication or delayed publication of registered randomized trials on vaccines, and to investigate potential determinants of delay to publication. Design Survey.Data sources Trials registry websites, Scopus, PubMed, Google. Main outcome measures Publication status of trial results and time from completion to publication in peer reviewed journals. Study selectionData synthesis Cox proportional hazards regression was used to evaluate potential predictors of publication del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(15 reference statements)
1
0
0
Order By: Relevance
“…We found that the clinical trial data from 75% of abstracts reporting randomized trials and from 54% of those describing nonrandomized trials were published by March 2015, a statistically significant difference (p , .001). Our 75% rate of publication for abstracts reporting randomized trials in the ASCO database from 2009-2011 is similar to the 56%-91% reported by others who assessed rates of publication of randomized or large trials [1,9,[22][23][24][25][26][27]. Our finding that clinical data from only 54% of abstracts reporting on nonrandomized trials had been published 4-6 years after their ASCO submissions is consistent with the 56%-74% reported by others 5-7.5 years after publication of the abstract [9,10].…”
Section: Discussionsupporting
confidence: 81%
“…We found that the clinical trial data from 75% of abstracts reporting randomized trials and from 54% of those describing nonrandomized trials were published by March 2015, a statistically significant difference (p , .001). Our 75% rate of publication for abstracts reporting randomized trials in the ASCO database from 2009-2011 is similar to the 56%-91% reported by others who assessed rates of publication of randomized or large trials [1,9,[22][23][24][25][26][27]. Our finding that clinical data from only 54% of abstracts reporting on nonrandomized trials had been published 4-6 years after their ASCO submissions is consistent with the 56%-74% reported by others 5-7.5 years after publication of the abstract [9,10].…”
Section: Discussionsupporting
confidence: 81%